Nickel-Cobalt Alloy Deposition on Iron Substrate Using Electroless Deposition in Deep Eutectic Solvent - Zaimi, M; Din, M.A.; Lau, K. T.; Othman, I. S.; Widodo, T. D. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Electroless deposition of Ni has been successfully done via deep eutectic solvent (DES) ionic liquid. In this study, a binary Ni-Co alloy is deposited on iron substrate using electroless deposition method in a DES ionic liquid. The DES was made from 2:1 ratio choline chloride-ethylene glycol mixture with various concentrations of nickel and cobalt salts. The coating surface hardness is measured using micro Vickers hardness tester. The coating surface morphology was observed using scanning electron microscope (SEM). Corrosion behavior of the coating in 3.5 wt% NaCl aqueous solution is evaluated using electrochemical measurement method. The thickness of the coating ranged in between 12 mm to 17 mm and shows compact and dense layer above iron surface. The coating made from higher Co to Ni salts ratio concentration in the DES exhibits higher hardness (202.36 Hv) compared to lower Co ratio coatings as well as pure Ni (185.38 Hv) and Co (196.72 Hv) coatings. The corrosion potential of Ni-Co alloy coating from 1:1 Ni to Co salts ratio DES has higher corrosion potential and shows passive oxidation surface compared to iron. Hence, the binary Ni-Co alloy deposition on iron improves the substrate’s surface hardness and corrosion resistance.